1995
DOI: 10.21273/jashs.120.6.1010
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock Effects on the Flowering of `Delicious' Apple. I. Bud Development

Abstract: Floral development was studied in buds of `Starkspur Supreme Delicious' apple trees growing on B.9, M.26 EMLA, M.7 EMLA, P.18, and seedling rootstocks. In each of 3 years, buds were sampled from the previous years growth at intervals throughout the growing season and dissected to determine whether the apex was domed, indicating the start of floral development. Number of bud scales and true leaves increased during the early part of the growing season, but remained fairly constant beyond 70 days after fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 16 publications
5
22
0
Order By: Relevance
“…In general, monopodial axes on ' M793 ' had the highest frequency of sylleptic shoots and the lowest flowering frequency. Dwarfing rootstocks have been reported to increase precocity [23]. In our study, all trees flowered in spring of year two, indicating no rootstock effect on precocity.…”
Section: Axillary Sylleptic Shoots Vs Floral Budsmentioning
confidence: 39%
“…In general, monopodial axes on ' M793 ' had the highest frequency of sylleptic shoots and the lowest flowering frequency. Dwarfing rootstocks have been reported to increase precocity [23]. In our study, all trees flowered in spring of year two, indicating no rootstock effect on precocity.…”
Section: Axillary Sylleptic Shoots Vs Floral Budsmentioning
confidence: 39%
“…However, Hirst and Ferree (1995) reported that the apical doming, as the indicator trait for floral initiation, generally occurs between 85 and 109 DAFB. Hoover et al (2004) conducted a similar study to determine the effect of cultivar on the course of organogenesis on apple buds and also showed that doming occurs at 86 to 112 DAFB.…”
Section: Discussionmentioning
confidence: 99%
“…Characterisation of floral initiation seems to be ambiguous because of some uncertainties on description of flowering stages. Dencker and Hansen (1994) reported that the doming of apex in apple basically coincides with the cessation of shoot growth, which has also been considered as the first sign for floral initiation (Hirst and Ferree 1995). Foster et al (2003) quantitatively analysed the diameter of SAM over its developmental course and showed that the apex broadening happens prior to its doming.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements ANATOMICAL MEASUREMENTS. The following measurements were made on sampled spurs: 1) spur and bourse leaf number and leaf area (LI-3000; LI-COR, Lincoln, NE), 2) stomatal density, and 3) flower formation [examined under a dissecting microscope (SZ-STS; Olympus Corp., Center Valley, PA)] to determine flower formation for each bourse (Hirst and Ferree, 1995b).…”
Section: Methodsmentioning
confidence: 99%